Impact of repeated in-vitro bacterial culture on virulence and antibiotic resistance characteristics: a study of Gram-positive and Gram-negative fish pathogens - Angana Bag; Vikash Kumar; Anupam Adhikari; Biswajit Mandal; Souvik Dhar; Basanta Kumar Das (Frontiers in Microbiology)
The ability of bacteria to respond to environmental changes is critical for survival. This enables them to withstand stress, form complex communities, and trigger virulence responses during host infections. In this study, we examined the effects of repeated in vitro subculturing on the virulence and antimicrobial resistance (AMR) profiles of Gram-negative and Gram-positive fish pathogens. The fish pathogenic bacterial isolates, namely Lactococcus lactis, Enterococcus gallinarum, Proteus penneri, and Escherichia coli, underwent 56 consecutive subcultures in tryptic soy broth and were evaluated for virulence, antimicrobial susceptibility, and AMR gene expression. The results revealed a significant decrease in the virulence of Gram-positive pathogens. Both L. lactis and E. gallinarum exhibited a marked reduction in the mortality rates of Labeo rohita after repeated subculturing, ultimately achieving 0% mortality by day 56. This suggests losing key virulence factors, such as toxins and adhesins, under non-selective conditions. In contrast, Gram-negative bacteria, particularly P. penneri and E. coli, exhibited higher levels of virulence throughout the study, even though mortality rates gradually declined. The antimicrobial resistance profiles of L. lactis remained steady, demonstrating consistent resistance to a wide range of antibiotics, including rifampicin and polymyxin B. Meanwhile, E. gallinarum showed slight variations in resistance, especially to colistin, while P. penneri and E. coli experienced changes in resistance to multiple antibiotics, including polymyxin B and tetracycline, after 42 days of subculturing. Importantly, no genetic alterations were detected in AMR-related genes through quantitative PCR analysis, indicating that the observed changes in resistance were likely phenotypic rather than genetic. This study underscores the critical need for ongoing surveillance in aquaculture pathogen management, emphasizing the dynamic nature of bacterial virulence and resistance profiles that can develop from prolonged subculturing.